2011
DOI: 10.1111/j.1469-8749.2010.03909.x
|View full text |Cite
|
Sign up to set email alerts
|

Autism in two females with duplications involving Xp11.22-p11.23

Abstract: We present two phenotypically similar females with Xp duplication who have autism and epilepsy. Case 1 is a 14-year-old Honduran female with autism and medically refractory complex partial, secondarily generalized epilepsy. Case 2 is a 3-year-old Austrian female with autism and medically refractory complex partial epilepsy. Both patients also share features of severe intellectual disability (case 1 has a developmental quotient of 23, case 2 has a developmental quotient of 42) and dysmorphic facial features. Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Interestingly, GRASP1 is an X-Chromosome gene located at Xp11.23, a region that has been previously associated with ID and autism (Chung et al, 2011; Edens et al, 2011; Giorda et al, 2009). We performed a screen on a cohort of well-characterized male probands (n=400) with ID and a pedigree consistent with X - I inked (XL) inheritance (Wu et al, 2007; Zhang et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, GRASP1 is an X-Chromosome gene located at Xp11.23, a region that has been previously associated with ID and autism (Chung et al, 2011; Edens et al, 2011; Giorda et al, 2009). We performed a screen on a cohort of well-characterized male probands (n=400) with ID and a pedigree consistent with X - I inked (XL) inheritance (Wu et al, 2007; Zhang et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical and genetic findings in the present Patients 1–5 and previously reported patients with overlapping, molecularly characterized duplications are summarized in Table and Figure . Of particular interest is a recurrent microduplication Xp11.22‐p11.23 of about 4.5 Mb reported previously in 11 female patients from eight families [Giorda et al, ; Chung et al, ; Family 1, Family 2, Case 4, Case 8, Case 9; Marshall et al, ; Case SK0306–004; Edens et al, ; Case 2] as well as a larger duplication of about 6 Mb in a further female which shares the distal breakpoint but has a different proximal breakpoint [Giorda et al, ; Case 5]. In 10 of these 12 females the XI pattern was analyzed and 7/10 cases showed a skewed inactivation (defined as >80% of one X‐Chromosome), all of them with preferential inactivation of the normal X. Giorda et al found a comparable phenotype in the patients known up to 2009 [Giorda et al, ] consisting of DD/ID, a particular speech impairment, often EEG anomalies (typically continuous spike waves during slow sleep and/or rolandic‐like spikes), and, in addition, overweight in half of the cases, and reported on a similar phenotype in two males with the recurrent duplication.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, small duplications of the proximal short arm of the X chromosome, in particular duplications encompassing Xp11.23, have been reported to be associated with neurodevelopmental disorders both in males and females [Bonnet et al, ; Froyen et al, ; Marshall et al, ; Monnot et al, ; Giorda et al, ; Holden et al, ; Chung et al, ; Edens et al, ; El‐Hattab et al, ]. Surprisingly, and in contrast to previously described larger duplications in Xp with selective inactivation of the aberrant X‐chromosome and a commonly normal phenotype in most carrier women [Matsuo et al, ], females with microduplications including Xp11.23 repeatedly showed preferential inactivation of the normal X‐chromosome.…”
Section: Introductionmentioning
confidence: 98%
“…These associated disorders are particularly interesting since we have identified RORA deficiency (specifically, reduced expression) in the phenotypic subtype of ASD associated with severe language impairment [13]. Using chromosome microarray analysis, Edens and colleagues reported duplications involving Xp11.22-p11.23, a region where HSD17B10 gene is located, in two females with autism and epilepsy [90]. …”
Section: Discussionmentioning
confidence: 99%